Pengaruh Motivasi dan Literasi Kewirausahaan Terhadap Minat Berwirausaha Pada Mahasiswa Peserta PMW Untag Surabaya - Desi Ramadhani; Awin Mulyati; Diana Juni Mulyati (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims to determine whether there is an influence of Motivation (X1) and Entrepreneurial Literacy (X2) on Entrepreneurial Interest (Y) in Students Participating in PMW Untag Surabaya. With the large number of unemployment problems, the Entrepreneurial Student Program is needed to improve entrepreneurial skills among students, so that it is hoped that it can encourage students to start and develop their businesses. This research has the title